2006
DOI: 10.1622/1059-8405(2006)22[219:tiomsi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mass School Immunization on School Attendance

Abstract: The purpose of this study was to assess the impact a free, on-site influenza immunization program could have on attendance in Title 1 schools. Four Title 1 elementary schools participated in the study. Students at 2 schools were offered free FluMist immunizations on site, and students at 2 control schools were not. Compliance on receiving FluMist was measured on the percentage of students participating after evaluating for medical exclusions. Documentation on the reason for absences at all 4 schools included s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Another study examined all-cause absenteeism over the entire 2004–2005 school year at two elementary schools in Indiana where LAIV was offered and two control elementary schools (Wiggs-Stayner et al, 2006). Overall, 47% (277/596) of students enrolled in SLIV schools were vaccinated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study examined all-cause absenteeism over the entire 2004–2005 school year at two elementary schools in Indiana where LAIV was offered and two control elementary schools (Wiggs-Stayner et al, 2006). Overall, 47% (277/596) of students enrolled in SLIV schools were vaccinated.…”
Section: Resultsmentioning
confidence: 99%
“…For example, SLIV programs also might protect teachers and staff either directly through vaccination or indirectly by reducing their exposure to ill students. Of the studies reviewed, one reported that LAIV was offered to teachers and staff (Wiggs-Stayner et al, 2006), but none reported data on absenteeism for teachers. Additionally, data from Japan (Reichert et al, 2001) and elsewhere (Ghendon et al, 2006) conclude that immunizing school children can protect communities against influenza, and recent data from the United States have suggested the possibility of a similar effect (Piedra et al, 2005; Piedra et al, 2007; Talbot et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Salmon’s research team found that school nurses were more likely than other school personnel to hold beliefs supporting the utility and safety of vaccines and that students attending school with a school nurse were significantly less likely than children attending schools without nurses to have immunization exemptions (odds ratio = 0.39; 95% confidence intervals [.28, .56]). In another study, students attending schools whose nurses offered on-site administration of the FluMist vaccine had significantly fewer days absent than students in schools that did not offer the vaccine ( p < .001; Wiggs-Stayner et al, 2006). While not statistically significant, Baisch and colleagues' (2011) study found that immunization compliance was much greater in schools with nurses than in schools without nurses.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, it has become important to consider the perspectives of key stakeholders, including teachers and school administrators, to fully appreciate these programs. Most published anecdotal reports describe SLIV programs only from the perspectives of school nurses and other health care professionals (HCPs; Borja, Amidon, Spellings, Franzetti, & Nasuta, 2009; Carpenter et al, 2007; Effler et al, 2010; Hull & Ambrose, 2011; Hull, Frauendienst, Gundersen, Monsen, & Fishbein, 2008; King, 2006; King et al, 2005; Li, Freedman, & Boyer-Chu, 2009; Mears, Lawler, Sanders, & Katz, 2009; Ransom, 2009; Wiggs-Stayner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%